O programa minha casa minha vida e o marco regulatorio urbanístico do munícipio : o caso de Araraquara - Balestrini, Milton (2016)
The Minha Casa Minha Vida Programme (My House My Life) was launched in April 2009 with anti-cyclical objectives, in order to counteract the effects of the crisis triggered by the bursting of the housing bubble in the United States in 2008 (the subprime crisis), which caused consequences for the global economy. The PMCMV, however, reduced attention to the objectives of PlanHab - National Housing Plan, calling for the urgent need to maintain the level of economic activity. After five years of operation, the program is intimately linked to the National Housing Policy, to the point that, in practice, it has replaced it. The amount of produced houses is impressive. The Caixa Econômica Federal, a public bank, as the founding manager of the Housing policies and the PMCMV, attached to the Ministry of Finance, apparently gives priority to economic and financial issues for the approval of projects, to the detriment of the priorities with the quality of the urban environment and housing production. These issues are delegated to small and larger towns, where the PMCMV is realized. Such towns do have the power to make demands of adjustments on the projects, according to their master plans and local regulations. What is found, however, in several towns of São Paulo, is that the projects are usually built in very contradiction to what is expected of a master plan or a democratic urban and housing management, as recommended by the Federal Housing Policies and Plans (PlanHab). This study aims to investigate it, through a case in Araraquara. As we go through a whole process of three PMCMV assemblies for low-income people, we will be able to verify the compliance with the laws and municipal urban guidelines, as well as the urban and social impacts, both for the town and for the population served by the MCMV Programme.